Sustainable Waste Recycling from the Fruit Pulp Industry Applied as an Adsorbent of Textile Dye - Mendes, Carolina Rosai [UNESP]; Dilarri, Guilherme [UNESP]; Stradioto, Marcia Regina [UNESP]; Schuch, Joyce Maria [UNESP]; Bidoia, Ederio Dino [UNESP]; Montagnolli, Renato Nallin (Springer Nature, 2022)
Dyes are the main contaminant from the textile industry wastes. Dyes can severely harm the environment, disturbing all the water cycle and organisms living in these environments. The juice industry generates waste of the peel from a great number of fruits. The peel of Passiflora edulis is rich in pectin, a polymer with great adsorption potential for textile dye sorption. However, the lack of applicability and adsorption interaction knowledge of the use of pectin as textile dye adsorbent makes it impossible to apply them, being necessary more studies with different dyes for its application and understanding of the chemical interactions of adsorbent/adsorbate. Thus, the aim of the present study was to evaluate the adsorptive potential of pectin present in the peel residue of P. edulis. Adsorption experiments were carried out to analyze the kinetics, isotherm, and thermodynamics, seeking the optimization of the adsorption treatment. Scanning electron microscopy and Fourier transform infrared spectrophotometry were used to characterize and analyze the main adsorption sites of the pectin from P. edulis peels. Bioassays using the Lactuca sativa seeds confirmed the reduction of the toxicity of the solution after the adsorption treatment. The results also confirmed a chemisorption occurrence, confirming the strong interaction between the pectin and the textile dye. Therefore, the material tested in the present study can potentially be applied for textile waste treatment, removing dyes from effluents, in addition to giving a noble destination for a residue from the juice industry.
Keywords: Biopolymer; Isotherm; Pectin; Peel of passion fruit; Synthetic dye